Sex-related spatial patterns of Poa ligularis in relation to shrub patch occurrence in northern Patagonia - Bertiller, Monica Beatriz (2000)
Poa ligularis is a dioecious species and a valuable forage plant which is widespread in the arid steppe of northern Patagonia (Argentina). The vegetation in these areas consists of a system of perennial plant patches alternating with bare soil areas defining contrasting micro-environments. We hypothesized that (1) male and female individuals of P. ligularis are spatially segregated in different micro-environments, (2) the intensity of spatial segregation of sexes depends on plant structure and (3) spatial segregation of sexes is enhanced by competitive interactions between the sexes within the vegetation patches. We analysed the spatial distribution of female and male individuals in relation to the spatial pattern of vegetation in two areas differing in their vegetation structure. The location of P. ligularis within patches where either male, female or both sexes occurred was also analysed. The results indicate that different patterns of spatial distribution of sexes of P. ligularis may be found at the community level depending on the dominant life forms and geometric structure of plant patches. Where patches are of a lower height, with a high internal patch cover, individuals of both sexes are concentrated within patch canopies. In sites characterized by large, tall patches and less internal patch cover suitable microsites for female and male P. ligularis occur both within and outside the patch with males located at further distances from the patch edge. Where the patch is large and tall enough to allow the establishment of males and females at relatively high numbers, males occupy the patch periphery or even colonize the interpatch bare soil. These spatial patterns are consistent with selective traits in which females better tolerate intraspecific competition than males, while males tolerate wider fluctuations in the physical environment (soil moisture, nitrogen availability, wind intensity, etc.).